Periosteum-Derived Micrograft in Sinus Floor Augmentation: A Literature Review - Esti Cahyani Adiati; Dimas Ilham Hutomo; Sri Lelyati C. Masulili (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction. Vertical deficiency due to maxillary sinus pneumatization in the posterior maxilla is a challenge for clinicians in dental implant placement. Sinus floor augmentation is a treatment procedure to overcome the vertical deficiency problem. Various regenerative materials have been used and developed for sinus floor augmentation, one of them is periosteum-derived micrograft (PDM) which derived from autogenous periosteum. Periosteum has pluripotent cells and a good proliferation rate that is useful for bone regeneration and potential for sinus floor augmentation. This literature review was conducted with the aim of investigating the use of PDM in sinus floor augmentation. Review. Sinus floor augmentation aims to achieve adequate bone height in the posterior maxilla by raising the sinus membrane and placing regenerative material before dental implant placement. Periosteal-derived micrograft is periosteal tissue which cut into smaller pieces and processed for use with scaffolds to heal bone defects. Micrograft have been shown to induce scaffold revascularization, express Wingless/Integrated (WNT-16) and periostin (POSTN), mesenchymal stem cell marker, pro-angiogenic factor and β-catenin gene involved in osteogenic differentiation, osteoblast maturation, and overall bone regeneration. PDM has the advantage of producing faster bone regeneration and shows good clinical results in sinus floor augmentation. Conclusion. Periosteum-derived micrograft has a good potential so it can be applied in sinus floor augmentation.